2019
DOI: 10.11591/edulearn.v13i3.12200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of students performances in biology: Implication for measurements and evaluation of learning

Abstract: Science education is believed to be a vital tool for individual and societal development at large. The persistent low levels of students' achievement in sciences at the various public examinations in Nigeria have continued to draw the attention of major stakeholders in education. This study examined academic achievement of Senior Secondary School students in biology and gender difference in students' achievement was examined. Ex-post facto design of descriptive research was adopted for the study. A proforma wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
1
13
1
Order By: Relevance
“…This finding is consistent with that of Kashu (2014), Nnenna, and Adukwu (2018). However, the finding is in contrast with that of Bozdoğan et al (2014), Okorie and Ezeh (2016), Bichi et al, (2019) who found that female students performed better than male students in science. Besides, the finding contradicts that of Olasehinde and Olatoye (2014), Ngozi et al (2018), Joseph and John (20 15), Ogbianigene (2014), Olasehinde and Olatoye (2014) who affirmed that gender differences do not affect students' academic achievement in the science subjects.…”
Section: Academic Performance Of Students In Biology By School Locationcontrasting
confidence: 89%
See 3 more Smart Citations
“…This finding is consistent with that of Kashu (2014), Nnenna, and Adukwu (2018). However, the finding is in contrast with that of Bozdoğan et al (2014), Okorie and Ezeh (2016), Bichi et al, (2019) who found that female students performed better than male students in science. Besides, the finding contradicts that of Olasehinde and Olatoye (2014), Ngozi et al (2018), Joseph and John (20 15), Ogbianigene (2014), Olasehinde and Olatoye (2014) who affirmed that gender differences do not affect students' academic achievement in the science subjects.…”
Section: Academic Performance Of Students In Biology By School Locationcontrasting
confidence: 89%
“…The urban school students performed better than the rural school students. This finding on school location still is in line with that of Olutola (2017), Umar (2017), Bichi et al (2019) in Biology. Similarly, there was a significant difference between the academic performance of students in rural and urban secondary schools in Basic Science in favor of urban school students (Awodun & Oyeniyi, 2018).…”
Section: Academic Performance Of Students In Biology By School Locationsupporting
confidence: 87%
See 2 more Smart Citations
“…One way to improve the quality of National Education in a better direction requires courage to take the policy of fixing the system used as a system of assessment tools [1]. Education is regarded as a key that unlocks the development of potential personal and national values and all other kinds of rights and powers in the world [2] Education in Indonesia as stated in the 1945 Republic of Indonesia's Constitution that every citizen has the same right to obtain education, this indicates that all people have equal opportunity to get education without exception [3] Schools are part of the government which seeks to implement regulations as a form of active role in building better human resources through education [4].…”
Section: Introductionmentioning
confidence: 99%